Modificación de conductas agresivas en niños y niñas de 10 a 12 años, de la unidad educativa Mena del Hierro, a través de la terapia cognitivo conductual. - Quinteros Flores, Andrea Patricia (2016)
The present project was applied to children aged 10 to 12 years old from the “Mena del Hierro School”, located in the city of Quito-Ecuador in the parish of Cotocollao. The intervention was born from the demand obtained by the authorities of the institution, who stated that there was a high level of aggressiveness from the children towards their classmates and authorities; this has generated an internal conflict and therefore a general disgusting inside the Institution. It is for this reason that, after speaking with each tutor of the respective degrees, the members of the workshops were selected, considering the different behavior disorders, in order to implement workshops, to modification the aggressive behaviors through the cognitive behavioral approach, to increase the tools to generate a greater number of assertive behaviors and therefore eliminate them. The intervention consists of two phases: the first called prior intervention in which the MESSY test was applied, with that it worked in groups of Therapeutic using cognitive behavioral techniques such as self-instruction, role play, card economy, Jacobson muscle relaxation; Later in the second phase called posterior intervention, the same test was applied again, using the results obtained in both moments, to perform a comparative statistical analysis. Lastly, the systematization of the experience was performed based on particular data sequenced from the sessions, in order to benefit future research that contains the same guidelines to prevent or improve the different errors or hits found.